Society of Behavioral Medicine (SBM) position statement: SBM supports retaining healthy school lunch policies - Buscemi, Joanna (Transl Behav Med, 2015)
Schools are recognized as venues for population-based health promotion and chronic disease prevention initiatives targeting children, and the school food environment is a central component. The Healthy, Hunger-Free Kids Act of 2010 utilized research-based findings and expert recommendations to significantly improve school lunch standards in the kindergarten to twelfth grade (K-12) setting to enhance the nutritional intake and ultimately the health of children. The new guidelines include increasing the availability of whole grains, fruits, and vegetables; requiring children to select a fruit or vegetable daily; and restricting serving sizes. There is currently no evidence that the revised standards have increased school lunch plate waste. However, there is evidence that children are consuming more healthful foods. The Society of Behavioral Medicine (SBM) supports retaining current school lunch standards set by the Healthy, Hunger-Free Kids Act of 2010. SBM also supports increasing the evidence-based by evaluating the implementation and impact of the school lunch revisions.